CONSIDERATIONS REGARDING THE FRETTING PHENOMENON USING LEAF SPRINGS - Stefan GHIMIȘI (Fiabilitate şi Durabilitate)
The fretting phenomenon represents particulary and complex form of wear who is; generaly, and/or weary of fretting who is produced on the load contact in a relative oscialatory movement lay small amplitude.A simultaneoustly applied tangential force and normal into contact appears a adhesion force